Analisis Stok dan Tingkat Pemanfaatan Sumberdaya Ikan Lemadang (Coryphaena hippurus) Berdasarkan Data di Pelabuhan Perikanan Samudera Cilacap - Cita Susila; Abdul Ghofar; Suradi Wijaya Saputra (Jurnal Kelautan Tropis, 2020)
Dolphinfish fish is one of the commodities of Indonesian waters, which is a bycatch of tuna fisheries. Lemadang fish are under considerable catching pressure and tend to increase, thus endangering their sustainability. The purpose of the study was to find out the length of first caught (Lc50%), growth parameters, mortality rate, MSY value, optimum trip (f) and lemadang fish exploitation rate. The data collected are fish length (cmFL), fish weight (kg), fish production, and fishing efforts. The data were collected once every 2 weeks during November 2019 until January 2020. The results of the study is the size of fish ranged from 41 – 125 cmFL and  length at first capture (Lc50%) 75 cmFL. The long-weight relationship analysis obtained equation W=0,0000378*L2,363 with negative allometric growth pattern. The growth equation von Bertalanffy obtained Lt = L∞(1-e-1.8(t+0,343)). The total mortality 8,54 year-1 the rate of exploitation amounted to 0,8 with the peak of recruitment in August. The estimated value of MSY of Dolphinfish was 121.570 kg/year with optimum effort of 571 trip/year. The estimated value of Dolphinfish sustainable potential is 121,570 kg/year, with optimum efforts of 571 trips/year. Dolphinfish production since 2011 has exceeded its maximum sustainable yield (MSY). Utilization of Dolphinfish fish resources has been overfishing, both based on analysis of analytical models and production surplus models. Ikan Lemadang merupakan salah satu komoditi dari perairan Indonesia, yang merupakan bycatch dari perikanan tuna. Ikan Lemadang mengalami tekanan penangkapan yang cukup tinggi dan cenderung meningkat, sehingga dapat membahayakan kelestariannya. Tujuan dari penelitian adalah mengetahui ukuran pertama kali tertangkap, parameter pertumbuhan, laju mortalitas, nilai MSY, trip (f) optimum, dan tingkat eksploitasi ikan Lemadang. Data yang dikumpulkan adalah panjang cagak ikan (cmFL) dan bobot ikan (kg), volume tangkapan dan upaya penangkapan (trip), produksi ikan dan trip penangkapan. Pengambilan data dilakukan 2(dua) minggu sekali selama bulan November 2019 hingga Januari 2020. Hasil penelitian diperoleh ukuran panjang ikan berkisar 41 – 125 cmFL, dan ukuran pertama kali tertangkap (Lc50%) 75 cmFL. Persamaan hubungan panjang-bobot didapatkan W=0,0000378*L2,363,dan sifat pertumbuhan alometrik negatif. Persamaan pertumbuhan von Bertalanffy ikan Lemadang didapatkan Lt = L¥ (1-e-1,8(t+0,343)). Puncak rekrutmen terjadi pada bulan Agustus. Laju mortalitas total (Z) adalah 8,54 per tahun, mortalitas penangkapan (F) = 6,81/tahun, dan tingkat eksploitasi (E=F/M) sebesar 0,8. Nilai dugaan potensi lestari ikan Lemadang sebesar 121.570 kg/tahun, dengan upaya optimum sebesar 571 trip/tahun. Produksi ikan Lemadang sejak tahun 2011 sudah melebihi tingkat produksi maksimum lestari (MSY)-nya. Pemanfaatan sumber daya ikan Lemadang sudah overfishing. baik berdasarkan analisis model analitik maupun model surplus produksi.